Survey Tingkat Vo2 MAX pada Atlet Selam Dragon Wira Yuda Kediri Tahun 2021 - Ahmad Nuri; Imam Sugeng (PT FORMOSA CENDEKIA GLOBAL, 2022)
One component of the athlete's physical condition is endurance. With good endurance, the athlete's performance in the competition will increase. The purpose of this study: to provide information to coaches and athletes about the VO₂Max level of Dragon Wira Yuda Diving Athletes in 2021. The results of this study are expected to be useful for athletes and readers. This research method is descriptive quantitative. The population in this study, namely the Dragon Wira Yuda Diving Athlete, amounted to 12 athletes. This research instrument uses the Multistage Fitness Test (MFT). The results of the analysis of VO₂Max data for the Dragon Wira Yudha Kediri athlete in the diving (finswimming) branch, the majority were categorized as LESS with men level 6 turning 8 with a score of 35.87, while for female athletes level 5 turning 7 with a value of 32.4 aerobic capacity (VO2MAX).